Republic of Armenia : Fourth Review Under the Extended Arrangement and Request for Waiver and Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Armenia. (IMF Staff Country Reports; Country Report, 2016)
This paper discusses Armenia's Fourth Review Under the Extended Arrangement and Request for Modification of Performance Criteria. Growth is expected to reach about 2.5 percent in 2016, as the external environment continues to be weak and the effects of past positive one-off factors dissipate. Domestic demand is expected to remain subdued and inflation to remain slightly negative by end-year. The headline fiscal deficit is expected to widen to nearly 6 percent of GDP, although the cyclically adjusted primary balance is projected to fall slightly vis-a-vis 2015. The IMF staff supports completion of the review and the authorities' request for a purchase in the amount equivalent to SDR 15.65 million.